Intellectual capital efficiency and economic value added: a comparative study / Naqiah Awang - Awang, Naqiah (2015)
This study explores and compares intellectual capital efficiency and its four components (human, structural, innovation and physical capital) among ASEAN manufacturing firms in emerging country (Malaysia) and developed country (Singapore). Furthermore, this study examines the association between intellectual capital efficiency measured by Modified Value Added Intellectual Coefficient (MVAIC) and firm financial performance measured by EVA of these two countries.In extension of their direct effect, this study investigates the moderation effect of new product introduction on the association between the construct. This cross sectional quantitative study has drawn data from 56 manufacturing Malaysian and Singaporean firm for three years, which make up total sample of 168 observations. Data were gathered from sampled firms annual report and Osiris Database. The content analysis method was employed to collect data of new product introduction. The Independent sample t-test and regression analysis have been utilized in providing empirical evidence about the objectives. The findings revealed that there is no significant different in the means score of MVAIC and its three components (human, structural and physical capital) across these two countries except for innovation capital. Further findings indicated there is a negative significant association between MVAIC particularly HCE with EVA, implying that firm with greater IC efficiency will reduce value of shareholders. Nevertheless, firms properly manage their IC and providing support for resource based theory, thus it is not the reason behind this negative linked. New product introduction was found not moderates the relationship between MVAIC and EVA. In addition, human capital exhibited largest contribution towards IC efficiency, while physical and financial capital found to be less contributing towards IC value creation. The result from this comparative study provides tools for shareholder's investment decision making and assist practitioners to find effective way in developing and managing IC capabilities to generate value for their business.